PEMBELAJARAN PERMAINAN BOLAVOLI DENGAN PENDEKATAN MODIFIKASI (Pada Siswa-Siswi Kelas VII SMP Negeri 23 Surabaya) Tahun ajaran 2017 / 2018) - Iswayudi, Nanda; Sugeng, Imam (LPPM Universitas Kahuripan Kediri, 2020)
AbstrakPermasalahan yang mendasar dalam pembelajaran permainan bolavoli pada siswa siswi di SMP adalah guru masih menggunakan peralatan sesungguhnya. Dimana peralatan yang biasanya digunakan oleh orang dewasa. Salah satu cara untuk mengatasi permasalahan dan untuk mempermudah adalah dengan menggunakan pendekatan modifikasi. Penelitian ini adalah penelitian kualitatif. Sedangkan metode yang digunakan adalah observasi dan wawancara. Observasi dilakukan untuk mengetahui proses pembelajaran permainan bolavoli. Kegiatan observasi ini dibagimenjadi 3 tahap dengan tujuan untuk memperbaiki tindakan selama proses pembelajaran permainan bolavoli dengan pendekatan modifikasi. Dimana pada tahap pertama adalah observasi sarana dan prasarana, serta proses pembelajaran permainan bolavoli sebelum diadakan penelitian. Tahap kedua, pembelajaran permainan bolavoli dengan pendekatan modifikasi tahap I. Tahap ketiga,pembelajaran permainan bolavoli tahap II yang merupakan perbaikan dari proses pembelajaran permainan bolavoli tahap I. Hasil penelitian didapatkan bahwa berdasarkan hasil pengamatan akhir dan hasil wawancara langsung dengan guru dan siswa-siswi, Pembelajaran permainan bolavoli dengan pendekatan modifikasi dapat mempermudah, senang dan gembira dalam proses pembelajaran serta penyampaian materi atau proses pembelajaran menjadi lebih variatif. Kata Kunci: Pembelajaran Voli, Metode Modifikasi THE TEACHING OF VOLLEY BALL GAME BY MODIFICATION APPROACH (For students of the third class at SMP 23 Surabaya of 2017/2018 academic year)The basic problem in teaching of volley ball game for the junior high school students is when the teacher is sting using the real equipments that must be used by the adult people. One of the solutions to solve this problem and to ease it is by using modification approach. Where by the main emphasize from the physical education is to make the students to be glad and happy. Since of that, it is hoped that by using the modification approach in teaching the volley ball game can make the students are so comfortable to join the teaching and learning process. This research has an objective to find the advantages of the teaching of volley ball game using modification approach for the third grade students at SMP 23 Surabaya. This research has an objective to know the teaching of volley ball game using modification approach for the third grade students at SMP 23 Surabaya. This research used the qualitative research. While the method used were the observation and also interviews. Observation was done to know the process of the divided in to three steps by the goals to repair the activity during the teaching of volley ball game using modification approach. The first step is means and placements and the teaching process of volley ball game before doing the research. The second step is by using modification approach step 1. The third step is the teaching of volley ball at the second step is reparation of teaching process of volley ball at the first step. The result of the research can be concluded that based on the last observation result andthe direct interview result between the teacher and the students. The implementation of teaching volley ball using modification approach can ease the delivering of lesson materials so the students will be more eager and energetic, glad and happy in teaching and learning process and also the delivering materials to be more various. Key words: teaching volleyball, modification method